2021
DOI: 10.1093/jb/mvab006
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoskeleton proteins for nuclear dynamics

Abstract: The eukaryotic nucleus shows organized structures of chromosomes, transcriptional components and their associated proteins. It has been believed that such a dense nuclear environment prevents the formation of a cytoskeleton-like network of protein filaments. However, accumulating evidence suggests that the cell nucleus also possesses structural filamentous components to support nuclear organization and compartments, which are referred to as nucleoskeleton proteins. Nucleoskeleton proteins including lamins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The Arp2/3 complex acts as an actin polymerizer in response to DNA damage, but Arp4, present in the nucleus, suppresses nuclear actin polymerization. 214 Nuclear actin has been shown to interact with emerin and also with the two actin-binding sites of lamin A in INM. 215,216 Utilization of the nuclear actin probe, nuclear Actin Chromobody (nAC), a novel molecular method to visualize actin dynamics inside the nucleus, revealed that integrin signaling is the driving force for nuclear actin polymerization via the LINC complex.…”
Section: Nuclear Actin Filamentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Arp2/3 complex acts as an actin polymerizer in response to DNA damage, but Arp4, present in the nucleus, suppresses nuclear actin polymerization. 214 Nuclear actin has been shown to interact with emerin and also with the two actin-binding sites of lamin A in INM. 215,216 Utilization of the nuclear actin probe, nuclear Actin Chromobody (nAC), a novel molecular method to visualize actin dynamics inside the nucleus, revealed that integrin signaling is the driving force for nuclear actin polymerization via the LINC complex.…”
Section: Nuclear Actin Filamentmentioning
confidence: 99%
“…Formin, an actin‐binding protein, is responsible for nuclear actin polymerization. The Arp2/3 complex acts as an actin polymerizer in response to DNA damage, but Arp4, present in the nucleus, suppresses nuclear actin polymerization 214 . Nuclear actin has been shown to interact with emerin and also with the two actin‐binding sites of lamin A in INM 215,216 .…”
Section: Mechanosensing At the Nucleus: Role Of Nucleoskeletonmentioning
confidence: 99%
“…Actin in the nucleus is referred to as nuclear actin. Nuclear actin is involved in a variety of nuclear events, including transcription, chromatin remodelling and DNA damage repair [22,80,81]. Actin dynamically changes its polymerized state between a monomeric globular actin and a polymeric filamentous actin (Factin).…”
Section: Nuclear Actinmentioning
confidence: 99%
“…The most studied nucleoskeleton proteins, lamins, are associated with chromosomal components termed lamina‐associated domains (LADs) [21]. Nuclear actin is also regarded as an emerging key player for organizing nuclear and chromatin structures [22].…”
Section: Introductionmentioning
confidence: 99%